Minority issues - Caflisch, Lucius (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2017)
This paper retraces the origins and the development of international minority protection by the League of Nations and the United Nations. It describes local and regional mechanisms of protection, such as that established by the European Human Rights Convention. It also shows how the European Court of Human Rights has protected Roma and Travellers in different areas, such as the prohibition of torture, the treatment of asylum seekers and beggars, the protection of property, the right to education and the exercise of political rights. Minority-specific treaties and mechanisms may improve the situation of minority groups, while human rights mechanisms will protect the rights of their individual members.
Keywords: človekove pravice; human rights; Evropska konvencija za človekove pravice; Helsinška konferenca; Društvo narodov; pravica do življenja; zaščita manjšin; politične pravice